Colonialism, Epistemic Injustice and Global Justice. Issue 3 (20th March 2014) - Collste, Göran
<x xml:space="preserve">Abstract</x> So far the discussion on global justice has mainly focused on global distributive justice. When the legacy of colonialism is taken into account, we could foresee a turn to global rectificatory justice.<boxed-text content-type="graphic" id="gpol12128-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>